A case report of local treatment of inoperable squamous cell lung carcinoma with convex-probe endobronchial ultrasound-guided intratumoral injection of cisplatin in a patient with severe COPD. Issue 24 (June 2017) - Li, Xiaochen; Liu, Xiansheng; Rao, Xiaoling; Zhao, Jianping; Xu, Yongjian; Xie, Min
Abstract: Rationale: Endobronchial ultrasound as a powerful diagnostic technology can also be used to perform intratumoral chemotherapy for extraluminal tumor. Patient concerns: A 69-year-old man with chronic obstructive pulmonary disease (COPD) presented with worsening dyspnea. A pulmonary function test showed severe airway obstruction and that forced expiratory volume in 1 s was 43% of the predicted value after a bronchodilator. Diagnoses: A bronchoscopy and histopathological analyses revealed a squamous cell carcinoma mostly located outside of the lumen with central airway obstruction. Interventions: Due to the poor pulmonary function, he cannot tolerate conventional active treatments, such as surgery, full dose systemic chemotherapy, or radiotherapy. Local treatments including argon plasma coagulation, cryotherapy, and bronchoscopic endobronchial intratumoral chemotherapy with cisplatin were performed to debulk intraluminal component of the tumor and recanalize occlusive airways in the left upper lobe. Convex-probe endobronchial ultrasound-guided transbronchial needle injection (EBUS-TBNI) delivered cisplatin into the extraluminal component of the tumor to relieve the symptom of dyspnea and opened up the opportunity for systemic chemotherapy without severe systemic complications. Outcomes: The patient had a good response to the comprehensive therapy of 4 cycles of low-dose intravenous chemotherapy and bronchoscopic interventions. Lessons: EBUS-TBNI is proven an effective and safe method to treat inoperable extraluminal central pulmonary carcinoma complicated with severe COPD. In the future, EBUS-TBNI may offer more treatment indications outlined in the existing publications.